The Role of Transocular Ultrasound in the Assessment of Neurotoxicity-Related Encephalopathy in Mushroom Poisoning - (:unkn) unknown (AVES, 2020)
Objective: Mushroom poisonings can lead to life-threatening organ dysfunctions and neurotoxicity-related encephalopathy. This study aimed to detect increased intracranial pressure by measuring optic nerve sheath diameter (ONSD) ultrasonographically and to determine its association with clinical and laboratory parameters. Methods: In this prospective case-control study, we evaluated the patients aged above 18 years who presented to the emergency department with mushroom poisoning. Vital signs, clinical and laboratory parameters and ONSD of both eyes measured with transocular ultrasound were noted at initial admission and the 24th hour. Results: We measured ONSD in 26 cases with mushroom poisoning and 26 healthy volunteers. Baseline ONSD measurements of the poisoning group were significantly higher than those of the control group (5.94 +/- 0.73 vs. 4.11 +/- 0.64, p<0.0001). ONSD values significantly regressed at 24th hour compared with the baseline measurements in the poisoning group (5.94 +/- 0.73 vs. 5.06 +/- 0.56, p<0.001). The ONSD values were significantly higher in patients who had a clinical picture of encephalopathy compared with patients who didn't have (6.05 +/- 0.72 vs. 4.36 +/- 1.03, p<0.001). No significant deterioration was observed in ammonium levels, hepatic and renal functions of the patients. Conclusion: We detected increased ONSDs in patients with mushroom poisoning compared with those in the control healthy volunteers. Our findings suggest that ONSD, measured by ultrasonography, may be safely and effectively used to diagnose transient encephalopathy associated with neurotoxicity.
Keywords: Encephalopathy; mushroom poisoning; neurotoxicity; transocular ultrasound; OPTIC-NERVE SHEATH; INTRACRANIAL HYPERTENSION; DIAMETER; MANAGEMENT; EPIDEMIOLOGY; SEVERITY; PRESSURE; EDEMA